Bacterial Long-Range Warfare: Aerial Killing of Legionella pneumophila by Pseudomonas fluorescens - Marie-Hélène Corre; Anne Mercier; Mathilde Bouteiller; Alix Khalil; Christophe Ginevra; Ségolène Depayras; Charly Dupont; Meg Rouxel; Mathias Gallique; Laettitia Grac; Sophie Jarraud; David Giron; et al. (Microbiology Spectrum, 2021)
ABSTRACT Legionella pneumophila, the causative agent of Legionnaires’ disease, is mostly found in man-made water systems and is one of the most closely monitored waterborne pathogens. With the aim of finding natural ways to control waterborne pathogens and thus further reduce the impact of disinfection by-products on human health, some studies have demonstrated the ability of bacteria to kill Legionella through the production of secondary metabolites or antimicrobial compounds. Here, we describe an unexpected growth inhibition of L. pneumophila when exposed to a physically separated strain of Pseudomonas fluorescens, designated as MFE01. Most of the members of the Legionellaceae family are sensitive to the volatile substances emitted by MFE01, unlike other bacteria tested. Using headspace solid-phase microextraction GC-MS strategy, a volatilome comparison revealed that emission of 1-undecene, 2-undecanone, and 2-tridecanone were mainly reduced in a Tn5-transposon mutant unable to inhibit at distance the growth of L. pneumophila strain Lens. We showed that 1-undecene was mainly responsible for the inhibition at distance in vitro, and led to cell lysis in small amounts, as determined by gas chromatography-mass spectrometry (GC-MS). Collectively, our results provide new insights into the mode of action of bacterial volatiles and highlight them as potent anti-Legionella agents to focus research on novel strategies to fight legionellosis. IMPORTANCE Microbial volatile compounds are molecules whose activities are increasingly attracting the attention of researchers. Indeed, they can act as key compounds in long-distance intrakingdom and interkingdom communication, but also as antimicrobials in competition and predation. In fact, most studies to date have focused on their antifungal activities and only a few have reported on their antibacterial properties. Here, we describe that 1-undecene, naturally produced by P. fluorescens, is a volatile with potent activity against bacteria of the genus Legionella. In small amounts, it is capable of inducing cell lysis even when the producing strain is physically separated from the target. This is the first time that such activity is described. This molecule could therefore constitute an efficient compound to counter bacterial pathogens whose treatment may fail, particularly in pulmonary diseases. Indeed, inhalation of these volatiles should be considered as a possible route of therapy in addition to antibiotic treatment.